Development of immature stages and comparative demography of two cucurbitattacking fruit flies in Reunion island: Bactrocera cucurbitae and dacus ciliatus (Diptera Tephritidae) - Vayssières, Jean-François; Carel, Y.; Coubes, M.; Duyck, P.F. (2008)
On Reunion Island, two species of Dacini, Bactrocera cucurbitae (Coquillett) and Dacus ciliatus Loew, infest 16 host plant species belonging to the family Cucurbitaceae from sea level to 1,600 m. These two species represent two primary pests of this plant family on the island. Melon fly, Bactrocera cucurbitae, and Ethiopian fruit fly, D. ciliatus, larval development was studied at four different constant temperatures (15, 20, 25, and 30°C) with three host plants (cucumber, pumpkin, and squash). Adult life histories of these two species were studied at 25°C with the three host plants. The results led to the conclusion that B. cucurbitae had a faster egg incubation time. Its preimaginal instars developed significantly faster than those of D. ciliatus independent of temperature. B. cucurbitae and D. ciliatus had similar mean preoviposition duration and egg hatching success. Fecundity was significantly higher for the melon fly on cucumber and pumpkin and lower on squash. Two distinctly different life- history patterns were evident: (1) later onset of reproduction, longer oviposition time, longer life span, and higher fecundity (B. cucurbitae) and (2) early reproduction, lower oviposition time, shorter life span, and lower fecundity (D. ciliatus). These results are useful for improving laboratory-rearing methods and for building simulation models to predict Dacini population dynamics.